Impact of preoperative intraocular pressure on corneal endothelial cell loss after phacoemulsification in acute primary angle-closure glaucoma with cataracts - Shen, Jiaqi; Liu, Xin; Lin, Mingyue; Shao, Yuting; Niu, Guozhen; Qu, Shen; Niu, Yunli; Zhou, Qi; Zhang, Li; Bi, Yanlong (Frontiers in Medicine, 2025)
PurposeThis study aimed to assess corneal endothelial cell loss (ECL) following phacoemulsification and intraocular lens implantation (Phaco+IOL) in eyes with acute primary angle-closure glaucoma (APACG) and cataracts under different preoperative intraocular pressure (IOP) levels.MethodsThis non-randomized controlled trial included 75 eyes from 75 patients with APACG and cataracts who underwent Phaco+IOL. All patients received pharmacotherapy and anterior chamber paracentesis before surgery and were grouped according to their preoperative IOP: the high-IOP group (IOP ≥ 25 mmHg) and the IOP-controlled group (IOP < 25 mmHg). IOP, visual outcome, endothelial cell density (ECD), hexagonality (HEX), coefficient of variation (CV), and central corneal thickness (CCT) were evaluated up to 3 months postoperatively. Baseline ECD, HEX, and CV parameters were measured in the contralateral eyes of all patients as a reference and compared with the postoperative results.ResultsThe average IOP decreased from 43.2 ± 4.8 mmHg to 16.5 ± 5.8 mmHg (p < 0.001) in the high-IOP group and from 18.3 ± 4.3 mmHg to 14.3 ± 3.2 mmHg (p < 0.001) in the IOP-controlled group on the first postoperative day. The changes in IOP were more significant in the high-IOP group (p < 0.001). The ECD at 3 months was 1705.2 ± 503.8 cells/mm2 in the high-IOP group and 2091.8 ± 330.1 cells/mm2 in the IOP-controlled group (p < 0.001). The ECL rates at 3 months were 35.0% (high-IOP group) and 17.4% (IOP-controlled group) (p < 0.001). The postoperative changes in HEX and CV at 3 months were more significant in the high-IOP group (p < 0.001; p = 0.003). Both groups produced comparable improvements in visual acuity and IOP.ConclusionUncontrolled high IOP (≥ 25 mmHg) before Phaco+IOL in patients with APACG and cataracts is associated with a higher rate of ECL. The rapid and substantial reduction of IOP during surgery may exacerbate corneal endothelial cell loss.Clinical trial registrationClinicalTrails.gov, identifier ChiCTR2100052096.